Investigation of chemical composition and crystal structure in sintered Ce15Nd15FebalB1 magnet - Shu-lin Huang; Hai-bo Feng; Ming-gang Zhu; An-hua Li; Yue Zhang; Wei Li (AIP Advances, 2014)
The substitution of cerium, a more abundant rare-earth element, for sintered Nd-Fe-B magnets has drawn intense interest. In the present work, nominal composition of Ce15Nd15FebalB1 (wt. %), with cerium constitutes increased to 50% of the total rare-earth content, was used. And Ce-free Nd30FebalB1 (wt. %) was prepared by the same preparation process as comparison. The microstructure of the sintered magnets has been investigated by means of X-ray diffraction and transmission electron microscope. The results show that there are three kinds of RE-rich phases in the same magnet, i.e., fcc-(Ce,Nd)Ox (a=0.547nm), hcp-(Ce,Nd)2O3 (a=0.386nm, c=0.604nm) and bcc-(Ce,Nd)2O3 (a=1.113nm). Ors of (140)(Ce,Nd)2Fe14B// (1-21)bcc-(Ce,Nd)2O3(∼3°), [001](Ce,Nd)2Fe14B// [-214]bcc-(Ce,Nd)2O3; (01-1)(Ce,Nd)2Fe14B// (101)fcc- (Ce,Nd)Ox(∼2°), [101](Ce,Nd)2Fe14B// [12-1]fcc-(Ce,Nd)Ox were found through selected area electron diffraction (SAED) analysis. According to the analysis, it can be concluded that cerium has partly substituted for neodymium by occupying the corresponding atom sites in the Ce15Nd15FebalB1 magnet, without changing the crystal configuration.